Brief communication "Tree impacts into a flexible rockfall protection system" - A. Volkwein; A. Vogel; W. Gerber; A. Roth (Natural Hazards and Earth System Sciences, 2011)
In hilly terrain, on account of both timber exploitation as well as severe storms, fallen tree trunks can begin to slide, thus constituting a source of danger for people and infrastructure. Any flexible rockfall protection system that is installed under such conditions should also be designed to withstand these unique loading conditions (falling trees). A series of tests was successfully conducted with free-falling trunks. The tests showed the behaviour of a rockfall protection system, also in comparison to similar rockfall events. Numerical simulations were performed to check performance against the field tests. It could be shown that barriers can be tested and designed for tree impacts according to similar rockfall impacts.